Tafonomia de tempestitos conchíferos amalgamados da formação Teresina em Rio Preto (Estado do Paraná, permiano médio, bacia do Paraná) e suas implicações paleoambientais - Neves, Jacqueline Peixoto; Rohn Davies, Rosemarie; Simões, Marcello Guimarães [UNESP] (My University, 2011)
The deposits of the Permian Teresina Formation are mainly characterized by fi ne-grained siliciclastic rocks and centimetric intercalations of tempestites (bioclastic sandstones and coquinas). Despite the relevance of the bivalve-rich carbonate beds of the Teresina Formation to paleoenvironmental studies, their taphonomy is still poorly studied. The fossil concentration studied in this work was found in a quarry in the city of Irati, Rio Preto district, Parana State. The fossil concentration is located in the middle/upper portion of the unit, far from the top. The studied bed is a bioclastic, intraclastic, peloidal, grainstone/ packstone, with abundant bivalve shell fragments, pelitic and micritic intraclasts, peloids, rare ooids and oncoids, as well as permineralized of Lycophyta microphylles and fish scales. The grains of this carbonate concentration show: high degree of time-averaging, variable degree of packing (dense to disperse), no sorting and chaotic orientation. Notably, the concentration includes a mixture of elements which are indicative of: a) restrictive, low energy, carbonate environment (peloids, ooids and oncoids); b) subaerial environment surrounding the main body of water (Lycophyta microphylles) and c) quiet-water environment punctuated by storm events, where the suspension-feeding bivalves thrived. At least four depositional events caused by storm fl ows were recorded. The amalgamated nature of the bed is a result of storm events in an intracratonic basin with very low seafl oor slope and low rates of sedimentation and subsidence.
Taphonomy of Condensed Shell Storm beds of the Teresina Formation in Rio Preto (State of Parana, Middle Permian, Parana Basin): Paleoenvironmental Implications.